2011
DOI: 10.1080/13032917.2011.556222
|View full text |Cite
|
Sign up to set email alerts
|

Brand personality and destination image of Istanbul

Abstract: This study investigates brand personality and destination image of Istanbul, Turkey and compares the perceived image and personality across different nationalities visiting the city. The survey instrument included quantitative and qualitative (open ended) items and questions to better understand the first-time visitors' individual perceptions. Text analysis was utilized to reveal experiential image patterns in qualitative data. Respondents were grouped into four segments depending on the geographic and cultura… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
75
0
14

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(95 citation statements)
references
References 34 publications
(57 reference statements)
2
75
0
14
Order By: Relevance
“…In order to extract sensory categories, the automatic option for a word count of STAS was used, followed by a manual process of aggregating words or expressions that were related to a specific, meaningful sensory impression, having as a reference the external five human senses. The latter process was first conducted by the main researcher and further verified by a second researcher, having as a reference the previous literature and empirical studies on senses in tourism (Gretzel & Fesenmaier, 2003Govers, Go, & Kumar, 2007;Pan & Ryan, 2009) and research using the STAS software (Guerreiro, 2012;Sahin & Baloglu, 2011). The latter studies focus on destination image studies using mixed methods and illustrate some of the potential of the software.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…In order to extract sensory categories, the automatic option for a word count of STAS was used, followed by a manual process of aggregating words or expressions that were related to a specific, meaningful sensory impression, having as a reference the external five human senses. The latter process was first conducted by the main researcher and further verified by a second researcher, having as a reference the previous literature and empirical studies on senses in tourism (Gretzel & Fesenmaier, 2003Govers, Go, & Kumar, 2007;Pan & Ryan, 2009) and research using the STAS software (Guerreiro, 2012;Sahin & Baloglu, 2011). The latter studies focus on destination image studies using mixed methods and illustrate some of the potential of the software.…”
Section: Data Analysis Methodsmentioning
confidence: 99%
“…Following the conventions of past research, this research employs a survey questionnaire to collect data on tourists' perception on the brand personality of Lenggong Valley Sahin and Baloglu, 2011). The survey is designed to gauge perception on five dimensions of brand personality in which there are 42 personality traits.…”
Section: Methodsmentioning
confidence: 99%
“…Besides that, the actual visit will also affect and change based upon the first hand information and experience to the particular destination. Previous research measures destination brand image based on three elements; which are cognitive, affective, and conation (Sahin and Baloglu, 2011). However, Pike (2008) found that the majority of researches on destination image focus too much on cognitive attributes but have neglected two elements which are affective and conation.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Turkish Strategic Plan for 2023, building city brands in the tourism sector is a parameter explicitly stressed out (Ministry of Culture and 8 Tourism, 2007a). Istanbul, in specific, is recognized as a 'strong card' for tourism development in Turkey (Sahin and Baloglu, 2011). The value of Istanbul as a destination is also portrayed by international arrivals in 2012 (Istanbul Culture and Tourism Directorate, 2014), along with the fact that arrivals outscored those of traditionally popular destinations, such as Rome (Euromonitor International, 2014).…”
Section: The Case Of Turkey: Istanbul As a Destination For Culture Anmentioning
confidence: 99%